IMPROVING STUDENTS’ LEARNING MOTIVATION IN READING COMPREHENSION USING RECIPROCAL TEACHING - Helmi Gunawan; Ratna Ratna (Jurnal VARIDIKA, 2019)
Teaching reading comprehension to the students is not easy. The teacher often finds a lot of students’ learning motivation problems from the students. The students’ problems are (1) students’ interest, (2) students’ effort, (3) self responsibility activity or persistence, (4) students’ optimal experiences; (5) reinforcement and teacher's method. One of the efforts to minimize the problems is by empowering the students in the learning process. One of the teaching techniques that can empower learners is Reciprocal Teaching Method. An action research was carried out and aimed at finding out whether Reciprocal teaching can improve the students’ learning motivation in reading comprehension in classroom when the teacher applies reciprocal teaching. Two cycles are applied. The data are taken by observing the learning process when an action is applied, by interviewing the learners involved, by giving questionnaires and by conducting interview. The finding of the research shows that Reciprocal Teaching Method can improve the students’ learning motivation in reading comprehension when it is applied.